Environmental footprint and life cycle costing of a family house built on CLT structure. Analysis of hotspots and improvement measures. (July 2021) - Lechón, Y.; la Rúa, C. de; Lechón, J.I.
Abstract: This paper has performed an environmental footprint assessment and a life cycle costing (LCC) of a single family house built using CLT structure with the objective of understanding the relevance of the environmental impacts associated to CLT buildings, identifying the main hotspots in the different impacts and investigating several measures to minimize them. The research analyses all the relevant environmental pressures in order to identify potential trade-offs and synergies of the improvement measures proposed. Additionally, a LCC was performed so that the costs arising in the different stages of the life of the building as well as the savings from the improvement measures can be assessed. The methodology used is the Product Environmental Footprint (PEF) a methodology based on the Life Cycle Assessment, and the Life Cycle Costing methodology, also using a life cycle approach. The main novelty of this research is the combined application of these two methodologies to a building scale. Results have shown that, the studied family house produces 34 kgCO2eq per square meter and year, mainly produced in the use phase of the building. However, in the wooden structure a total of 2.8 kgCO2eq /m 2 are temporarily stored. In general, the use phase accounts for most of the impacts with the notable exceptions of water. Normalized and weighed results showed however that construction impacts are of higher relevance than the use phase impacts due to the very relevant role of the water scarcity results. Results also showed that investments in insulation measures as well as the use of forced ventilation systems pay off in environmental and economic terms reducing the environmental footprint and the life cycle costs of the building. Best results were obtained with the use of PV panels that proved to significantly reduce the environmental footprint as well as the costs. Some potential trade-offs were identified in the case of the use of increased insulation thickness and the use of PV panels. In the short term, while the electricity sector becomes fully decarbonized, the installation of PV panels is the most environmentally and economically sound solution to improve sustainability of the building sector in Spain. Graphical abstract: Image 1 Highlights: 34 kg CO2eq per square meter and year are produce in the life cycle of a CLT building. Insulation and forced ventilation reduce the environmental footprint and the costs. The use of PV panels significantly reduces the environmental footprint and the costs. Environmental trade-offs exist when using increased insulation and PV panels.